Serotonin regulates mitochondrial biogenesis and function in rodent cortical neurons via the 5-HT2A receptor and SIRT1–PGC-1α axis - Fanibunda, S. E. (2019)
Mitochondria in neurons, in addition to their primary role in bioenergetics, also contribute to specialized functions, including regulation of synaptic transmission, Ca2+ homeostasis, neuronal excitability, and stress adaptation. However, the factors that influence mitochondrial biogenesis and function in neurons remain poorly elucidated. Here, we identify an important role for serotonin (5-HT) as a regulator of mitochondrial biogenesis and function in rodent cortical neurons, via a 5-HT2A receptor-mediated recruitment of the SIRT1–PGC-1α axis, which is relevant to the neuroprotective action of 5-HT. We found that 5-HT increased mitochondrial biogenesis, reflected through enhanced mtDNA levels, mitotracker staining, and expression of mitochondrial components. This resulted in higher mitochondrial respiratory capacity, oxidative phosphorylation (OXPHOS) efficiency, and a consequential increase in cellular ATP levels. Mechanistically, the effects of 5-HT were mediated via the 5-HT2A receptor and master modulators of mitochondrial biogenesis, SIRT1 and PGC-1α. SIRT1 was required to mediate the effects of 5-HT on mitochondrial biogenesis and function in cortical neurons. In vivo studies revealed that 5-HT2A receptor stimulation increased cortical mtDNA and ATP levels in a SIRT1-dependent manner. Direct infusion of 5-HT into the neocortex and chemogenetic activation of 5-HT neurons also resulted in enhanced mitochondrial biogenesis and function in vivo. In cortical neurons, 5-HT enhanced expression of antioxidant enzymes, decreased cellular reactive oxygen species, and exhibited neuroprotection against excitotoxic and oxidative stress, an effect that required SIRT1. These findings identify 5-HT as an upstream regulator of mitochondrial biogenesis and function in cortical neurons and implicate the mitochondrial effects of 5-HT in its neuroprotective action.